ISLAMIC ECONOMY IN «ISLAMIC STATE»: IS IT POSSIBLE? - R. I. Bekkin (Vestnik MGIMO-Universiteta)
Muslim scholars from Egypt and British India formulated the principles of Islamic economy in the second half of the 1940s. At the turn of the 1970s-1980s a number of countries (Sudan, Iran and Pakistan) attempted to Islamize their financial systems. However, in none of the three, the experiment was successful. Afterwards, the Muslim world has not undertaken to build a financial system based on the principles of Islamic economics and finance any more. However, interest in the application of individual institutions of the Islamic economy has not faded away. The article examines how the principles of Islamic economic doctrine were applied in the formation of the “state” budget in the terrorist entity “Islamic State” (IS). The author analyses the principal differences between the theoretical constructions of the Islamic economy and their practical implementation in the territories controlled by the IS. In fact, the IS implements a completely different concept of Islamic economy and Islamic finance (fundamentalist) from the one that was applied in a number of Muslim countries (modernist). Considering the practice of application of Islamic economic principles by the IS, the author of the article develops the thesis expressed in his earlier publications that there is no single universal Islamic economic doctrine that could be applied with some modifications in any society and in any jurisdiction. Moreover, the various interpretations of the economic provisions of Shariah can come into serious contradiction with each other. This is indicated, in particular, in the case of the IS, where, with the help of law-permitting institutions, they try to legalize activities that are illegal from the point of view of Shariah. Another important feature of the financial policy in the IS is the insignificant interest in modern Islamic financial institutions: banks, insurance (takaful) companies, etc. The author explains this as follows. In their attempt to build a caliphate, the ideologists of the IS and their followers take a traditionalist approach in which there is no place for institutions unknown in the 7th-13th centuries. For traditionalists, such institutions as Islamic banks, etc., formed in the second half of the XX century, are often unauthorized innovations (bida’).